A method for preparing super-hydrophobic nickel-based surface by continuous laser direct forming
Through low-energy ball milling and selective laser melting technology, the oxide particles are uniformly distributed on the surface of nickel-based high-temperature alloys, and the laser processing parameters are regulated, which solves the problems of complex and high cost of superhydrophobic nickel-based surface preparation process in the existing technology, and achieves wear resistance and resistance Superhydrophobic nickel-based surface preparation with improved corrosion and stability.
Patent Information
- Application Number
- CN202210539049.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-05-18
AI Technical Summary
The prior art requires low surface energy substance modification when preparing superhydrophobic nickel-based surfaces, which are complex in the process and high in cost, and have poor overall structure and attribute stability of components under the action of pulsed lasers.
The oxide particles are evenly distributed on the surface of nickel-based high-temperature alloy powder through low-energy ball milling technology, and laser processing parameters are regulated using selective laser melting technology to form a superhydrophobic nickel-based surface, avoiding the modification of low-surface energy substances, reducing costs and improving stability.
It realizes a superhydrophobic nickel-based surface that synergistically improves wear resistance and corrosion resistance, improves the stability and comprehensive performance of nickel-based high-temperature alloys and expands its application range.
Smart Images

Figure CN114932236B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of laser additive manufacturing of nickel-based high-temperature alloy surface functions, and specifically relates to a method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming. Background Art
[0002] Nickel-based high-temperature alloys are used in aero-engines, key hot-end components of spacecraft, turbine blades and other components at a ratio of up to 40%-60% due to their excellent room temperature / high temperature (650°C) mechanical properties, good high temperature oxidation resistance and corrosion resistance. With the continuous changes in the service environment of aero-engines, higher requirements are placed on the strength, toughness, hardness, wear resistance, high temperature oxidation and other properties of nickel-based alloys. Studies have shown that bionic super-hydrophobic surfaces, i.e. surfaces with a contact angle greater than 150° and a rolling angle less than 10°, have the advantages of corrosion resistance, wear reduction, drag reduction, surface self-cleaning, and antifreeze. Therefore, super-hydrophobic nickel-based surfaces provide an important way to improve their performance.
[0003] As nickel-based components become increasingly complex, laser additive manufacturing technology based on layer-by-layer stacking has gradually emerged, which can realize the integrated forming of complex integral components. In addition, laser also has broad application prospects in the construction of super-hydrophobic surfaces. Existing Chinese patent CN113001026A proposes a method for preparing a super-hydrophobic surface based on comprehensive regulation of femtosecond laser and temperature control aging, that is, by controlling the parameters of femtosecond laser to obtain a micro-nano multi-level composite array structure on the metal surface, and then comprehensively adjusting the temperature and time to achieve low surface energy modification, and finally preparing a super-hydrophobic surface. Chinese patent CN112358812A proposes to etch a lattice structure on the surface of a magnesium alloy by laser, and then chemically modify the magnesium alloy after laser processing to obtain a super-hydrophobic coating. Although the above methods can all obtain super-hydrophobic metal surfaces, they require low surface energy material modification, complex processes, high costs, and the overall structure and properties of the components are destroyed under the action of pulsed lasers, and the stability is poor.
[0004] The formation of metal super-hydrophobic surface is jointly determined by the roughening of surface structure and low surface energy. Changing the continuous laser process parameters can achieve directional regulation of component forming quality, microstructure and mechanical properties. On the other hand, the enhanced oxide diffusion has the effect of refining grains, which can not only significantly improve the comprehensive performance of the alloy, but also the oxide decomposes into O atoms under the action of laser, and O and Ni generate NiO, which can reduce the surface energy of the material; and O has a strong binding force with C in nickel-based alloys, so the water molecules adsorbed by the hydrophilic carboxyl groups in the nickel matrix will be replaced by oxygen, thereby realizing the construction of super-hydrophobic nickel-based surface and expanding the application range of nickel-based alloys. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming, which does not require any low surface energy material modification and can construct a super-hydrophobic nickel-based surface with synergistically improved wear resistance and corrosion resistance in one step.
[0006] The present invention achieves the above technical objectives through the following technical means.
[0007] A method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming comprises the following steps:
[0008] Step 1: Mixing micron-shaped spherical nickel-based high-temperature alloy powder and micron-shaped oxide uniformly based on a low-energy ball milling process to obtain a composite powder in which oxide particles are uniformly distributed on the surface of the nickel matrix;
[0009] Step 2: Based on the selective laser melting technology, the composite powder in step 1 is layered and stacked to form a super-hydrophobic nickel-based surface by adjusting the laser processing parameters.
[0010] In the above scheme, in step 1, the nickel-based high-temperature alloy powder is gas atomized, with an average particle size ranging from 10 to 50 μm, a sphericity of more than 95%, and a purity of more than 99.9%.
[0011] In the above scheme, in step 1, the particles of the micron oxide are irregular in shape, and the average particle size ranges from 0.5 to 5 μm.
[0012] In the above scheme, in step 1, the oxide is dispersed on the surface of the metal nickel by a low-energy ball milling process, wherein the mass percentage of the micron oxide is 5-15wt%.
[0013] In the above scheme, in step 1, the ball milling parameters are as follows: rotation speed 200-300 rpm, time 2-4 h, ball-to-material ratio 3:1, vacuum in the ball mill, and the composite powder remains nearly spherical after ball milling.
[0014] In the above scheme, the micron oxide is one or a mixture of Y2O3, La2O3, Al2O3 and ThO2.
[0015] In the above scheme, the laser processing parameters are: laser power P is 250-350W, scanning speed v is 800-1600mm / s, spot diameter d is 70μm, scanning spacing h is 30-100μm, powder layer thickness is 30~50μm, and a partitioned island scanning strategy is adopted.
[0016] In the above scheme, the partitioned island scanning strategy is to divide a plane into several squares with a side length of 1 mm, and rotate 67° between layers.
[0017] In the above scheme, the laser energy density is 100-150J / mm 3When the surface of the nickel-based alloy is heated, a multi-scale micro / nano rough structure is formed, in which the microstructure is spheroidized metallic nickel and the nanostructure is the second phase reinforced oxide and NiO particles.
[0018] In the above scheme, the selective laser melting technology in step 2 includes the following steps:
[0019] (i) creating a 3D solid model based on 3D modeling software, and slicing the 3D solid model based on path planning, with a layer thickness of 50 μm;
[0020] (ii) The slicing task in step (i) is imported into the computer of the selective laser melting equipment, a stainless steel substrate is installed in the forming cylinder, the mixed nickel-based composite powder is poured into the powder cylinder, the hatch is closed, argon gas is passed to remove oxygen in the cavity, the pressure in the cavity is maintained at 0.3-1atm, and the substrate preheating function is turned on to 200°C;
[0021] (iii) When the oxygen content in the cavity is lower than 10 ppm, turn on the continuous fiber laser with a power of 500 W and a wavelength of 1080 nm to start the forming experiment; set the powder supply to be greater than 50 μm, and the flexible powder spreading arm spreads a layer of nickel-based composite powder with a thickness of 50 μm on the substrate. The laser melts / solidifies the powder according to the path planning to form a two-dimensional plane; after completing a layer of scanning, the forming cylinder drops by a powder supply thickness, and the powder cylinder rises by a powder supply thickness; repeat the above steps to continue scanning the powder until the solid processing is completed.
[0022] According to the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The present invention uses laser additive manufacturing technology to form an oxide-enhanced nickel-based high-temperature alloy, and regulates the surface morphology and roughness of the nickel-based high-temperature alloy based on laser process parameters and the content of the reinforcing phase. Under the action of the laser, the oxide decomposes into O atoms, and O and Ni generate NiO, which reduces the surface energy of the material; at the same time, O has a strong binding force with C in the matrix, so that the water molecules adsorbed by the hydrophilic carboxyl groups in the nickel matrix will be replaced by O, thereby obtaining a super-hydrophobic surface. Therefore, a super-hydrophobic nickel-based surface can be constructed in one step under the multi-scale structure of spheroidized micron nickel / nanoparticles. This method does not require any subsequent modification of low-surface-energy materials, which reduces costs and is energy-saving and environmentally friendly.
[0024] (2) The super-hydrophobic surface of the nickel-based high-temperature alloy constructed by the present invention has excellent corrosion resistance and wear resistance, while improving the stability of the super-hydrophobic surface, giving the nickel-based high-temperature alloy high-performance / multifunctional characteristics, and has broad application prospects in the aerospace and marine fields.
[0025] (3) Laser additive manufacturing technology can form complex components, with strong process controllability and material universality, and has great reference value in the construction of other low surface energy metal superhydrophobic surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the construction method of superhydrophobic nickel-based surface;
[0027] Figure 2 The surface morphology of the nickel-based alloy in Example 1;
[0028] Figure 3 Surface roughness and contact angle of the nickel-based alloy in Example 1;
[0029] Figure 4 The surface density of the nickel-based alloy in Example 1;
[0030] Figure 5 Surface roughness and contact angle of the nickel-based alloy in Example 2;
[0031] Figure 6 Surface roughness and contact angle of the nickel-based alloy in Example 3;
[0032] Figure 7 Surface roughness and contact angle of nickel-based alloy in Comparative Example 1;
[0033] Figure 8 Surface roughness and contact angle of nickel-based alloy in Comparative Example 2;
[0034] Fig. 9 The forming quality of the nickel-based alloy in Comparative Example 2;
[0035] Fig.10 Contact angle of the nickel-based alloy surface in Comparative Example 3. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0037] In order to better explain the technical solution of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments: The following embodiments are implemented based on the technical solution of the present invention, and it should be understood that the protection rights of these inventions are not limited by these embodiments.
[0038] The present invention discloses a method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming. Based on laser additive manufacturing technology, a high-stability nickel-based high-temperature alloy super-hydrophobic surface with synergistically improved corrosion resistance and wear resistance is constructed. The principle is to disperse oxide particles on the surface of nickel-based high-temperature powder based on a low-energy ball milling process. Optimized laser process parameters: laser body energy density 100-150J / mm 3The super hydrophobic surface of nickel-based high-temperature alloy with an oxide content of 5-15wt% is formed by selective laser melting. Under the action of laser, the oxide decomposes into O atoms, O and Ni generate NiO, reducing the surface energy of the material; at the same time, O has a strong binding force with C in the matrix, so the water molecules adsorbed by the hydrophilic carboxyl groups in the matrix are replaced by O, forming a super hydrophobic surface of nickel-based high-temperature alloy under the multi-scale structure of spheroidized micron metal nickel / nano oxide. This super hydrophobic surface can capture 90-95% of air, generate an air film to prevent corrosive media from penetrating into the matrix, and the surface exhibits durability and high wear resistance.
[0039] Embodiment 1:
[0040] like Figure 1 As shown, the method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming according to the present invention comprises the following steps:
[0041] (1) atomizing spherical nickel-based high-temperature alloy powder with an average particle size of 10-50 μm; dispersing 10 wt% of irregular oxides on the surface of the nickel-based powder by a low-energy ball milling method to form a nickel-based composite powder;
[0042] (2) Use selective laser melting technology to form oxide-reinforced nickel-based high-temperature alloys. First, create a three-dimensional solid model based on three-dimensional modeling software, and slice the three-dimensional solid model based on path planning, with each layer set to 50μm; then, install a stainless steel substrate in the forming cylinder, pour the mixed nickel-based composite powder into the powder cylinder, pass argon gas to remove oxygen in the cavity, and maintain a positive pressure of 0.3atm. When the oxygen content is lower than 10ppm, turn on the laser to melt / solidify the powder according to the path planning to form a two-dimensional plane; the powder supply amount needs to be greater than 50μm. In this embodiment, the powder supply amount is set to 120μm. After each layer is scanned, the forming cylinder drops a powder supply thickness, and the powder cylinder rises a powder supply thickness. Repeat the above steps until the three-dimensional solid processing is completed. The laser power P is 300W, the scanning speed v is 1000mm / s, the powder layer thickness d is 50μm, the scanning spacing h is 50μm, and the laser body energy density is 120J / mm 3 The alloy surface forms a spheroidized micron nickel / nano oxide multi-scale rough structure (attached Figure 2 ), the surface roughness is 12.95 μm, at this time, the surface contact angle reaches 156.1° (attached Figure 3 ), water droplets can roll on the surface, achieving super hydrophobicity. On the other hand, under this parameter, the sample is dense and has no metallurgical defects (attached Figure 4 ).
[0043] Embodiment 2:
[0044] The present embodiment is different from the specific embodiment 1 in that the laser power is set to 250W, the scanning speed is 1600mm / s, the scanning interval is 50μm, the powder layer thickness is 30μm, and the laser body energy density is 104J / mm 3 , the oxide content is 5wt%, and the rest is the same as Example 1.
[0045] As attached Figure 5 As shown, the surface roughness of the nickel-based alloy is reduced to 10.21 μm, the contact angle is 151.5°, and the superhydrophobicity is still maintained.
[0046] Embodiment 3:
[0047] The present embodiment is different from the specific embodiment 1 in that the laser power is set to 350W, the scanning speed is 800mm / s, the scanning interval is 60μm, the powder layer thickness is 50μm, and the laser body energy density is 145J / mm 3 , the oxide content is 15wt%, and the rest is the same as Example 1.
[0048] As attached Figure 6 As shown, the surface roughness of the nickel-based alloy increased to 13.18 μm, the contact angle was 153.2°, and it still maintained superhydrophobicity.
[0049] Comparative Example 1:
[0050] The difference between this comparative implementation and the specific implementation 1 is that the laser body energy density is increased to 166 J / mm 3 , wherein the laser power is 200 W, the scanning speed is 600 mm / s, the scanning spacing is 40 μm, the powder layer thickness is 50 μm, and the rest is the same as in Example 1.
[0051] Attached Figure 7 The surface roughness and contact angle of the nickel-based high-temperature alloy in Comparative Example 1 show that the roughness is reduced to 7.81 μm, the contact angle is reduced to 115.1°, the surface is hydrophobic, but the super-hydrophobic property is lost, and water droplets adhere to the surface.
[0052] Comparative Example 2:
[0053] The difference between this comparative implementation and the specific implementation 1 is that the laser body energy density is reduced to 64J / mm 3 , wherein the laser power is 450W, the scanning speed is 2000mm / s, the scanning spacing is 70μm, the powder layer thickness is 50μm, and the rest is the same as Example 1.
[0054] Attached Figure 8The surface roughness and contact angle of the nickel-based high-temperature alloy in Comparative Example 2 show that the roughness increases to 14.98 μm, the contact angle decreases to 126.9°, the surface loses its super-hydrophobicity, the surface edge is uneven, cracks and other defects appear, and the forming quality is poor (see Appendix Fig. 9 ).
[0055] Comparative Example 3:
[0056] This embodiment differs from the specific embodiment 1 in that the mass fraction of oxide is reduced to 0, that is, no reinforcing phase is added, and the rest is the same as the embodiment 1.
[0057] Attached Fig.10 is the contact angle of the nickel-based high-temperature alloy surface in Comparative Example 3. The contact angle decreases to 71.1°, and the surface becomes hydrophilic.
[0058] Table 1 illustrates the effects of wear and corrosion resistance of the superhydrophobic nickel-based surface in various embodiments and comparative examples.
[0059] Table 1: Wear and corrosion resistance of superhydrophobic nickel-based surfaces in different embodiments and comparative examples of the present invention
[0060]
[0061]
[0062] Principle Analysis
[0063] When the volume energy density is 100-150J / mm 3 At 120J / mm 3 For example, the surface is composed of a multi-scale structure of spheroidized micron nickel / nano oxide particles, and the surface follows the Cassie-Baxter model: cosθ r =f1cosθ-f2, where θ r and θ are the contact angles on the rough and smooth surfaces, respectively; f1 and f2 are the surface fractions of the solid phase and the gas phase, respectively; f1+f2=1; it can be calculated that θ r =151.5°, θ=71.1°, so the values of f1 and f2 are 0.0915 and 0.9085 respectively, indicating that the surface of the nickel-based high-temperature alloy contains about 90.85% air at this volume energy density. The air film prevents water droplets from contacting the surface, so the contact angle is greater than 150°, and water droplets can easily roll off the surface, showing super hydrophobicity, with excellent super hydrophobicity and wear resistance. When the volume energy density is greater than 150J / mm 3 , i.e. 166J / mm 3 When the water droplet and the surface are in the Wenzel model: cosθ *=rcosθ, where θ* is the contact angle of the rough surface, r is the surface roughness factor, and θ is the contact angle on the smooth surface. Therefore, when θ>90°, the contact angle increases with the increase of surface roughness. When the volume energy density is <100J / mm 3 , i.e. 64J / mm 3 When the surface roughness increases, the contact angle decreases to 126.9°, and the wetting mechanism changes to the Wenzel model. This is because the O atoms decomposed by the oxides decrease under low energy density, so the C in the matrix easily forms hydrophilic carboxyl groups. In addition, the content of low surface energy NiO decreases, and the surface wetting mechanism changes.
[0064] In summary, the optimized laser energy density is 100-150J / mm 3 When the oxide ceramic content is 5-15wt%, a highly corrosion-resistant and wear-resistant super-hydrophobic nickel-based surface can be obtained.
[0065] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0066] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming, characterized in that: The steps include: Step 1: Based on the low-energy ball milling process, the micron spherical nickel-based high-temperature alloy powder and the micron oxide are evenly mixed to obtain a composite powder in which the oxide particles are evenly distributed on the surface of the nickel matrix; the ball milling parameters are as follows: rotation speed 200-300rpm, time 2-4h, ball-to-material ratio 3:1, vacuum in the ball mill, and the composite powder remains nearly spherical after ball milling; the oxide is dispersed on the surface of the metal nickel by low-energy ball milling, wherein the mass percentage of the micron oxide is 5-15wt%; wherein the micron oxide is one or more mixtures of Y2O3, La2O3, Al2O3 or ThO2; Step 2: Based on the selective laser melting technology, the composite powder in step 1 is layered and stacked to form a super-hydrophobic nickel-based surface by adjusting the laser processing parameters; Laser processing parameters: laser power P is 250-350W, scanning speed v is 800-1600mm / s, spot diameter d is 70μm, scanning spacing h is 30-100μm, powder layer thickness is 30-50μm, and partition island scanning strategy is adopted; laser body energy density is 100-150J / mm 3 A multi-scale micro / nano rough structure is formed on the surface of the nickel-based alloy, in which the microstructure is spheroidized metallic nickel and the nanostructure is the second phase reinforced oxide and NiO particles.
2. The method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming according to claim 1, characterized in that: In step 1, the nickel-based high-temperature alloy powder is gas-atomized, with an average particle size of 10 to 50 μm, a sphericity of more than 95%, and a purity of more than 99.9%.
3. The method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming according to claim 1, characterized in that: In step 1, the particles of the micron oxide are irregular in shape and have an average particle size of 0.5 to 5 μm.
4. The method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming according to claim 1, characterized in that: The partitioned island scanning strategy is to divide a plane into several squares with a side length of 1 mm, and rotate 67° between layers.
5. The method for preparing a super-hydrophobic nickel-based surface by continuous laser direct forming according to claim 1, characterized in that: The selective laser melting technology in step 2 includes the following steps: (i) creating a 3D solid model based on 3D modeling software, and slicing the 3D solid model based on path planning, with a layer thickness of 50 μm; (ii) The slicing task in step (i) is imported into the computer of the selective laser melting equipment, a stainless steel substrate is installed in the forming cylinder, the mixed nickel-based composite powder is poured into the powder cylinder, the hatch is closed, argon gas is passed to remove oxygen in the cavity, the pressure in the cavity is maintained at 0.3-1atm, and the substrate preheating function is turned on to 200°C; (iii) When the oxygen content in the cavity is lower than 10 ppm, turn on the continuous fiber laser with a power of 500 W and a wavelength of 1080 nm to start the forming experiment; set the powder supply to be greater than 50 μm, and the flexible powder spreading arm spreads a layer of nickel-based composite powder with a thickness of 50 μm on the substrate. The laser melts / solidifies the powder according to the path planning to form a two-dimensional plane; after completing a layer of scanning, the forming cylinder drops by a powder supply thickness, and the powder cylinder rises by a powder supply thickness; repeat the above steps to continue scanning the powder until the solid processing is completed.
